Analisis Komparasi Model Prediksi Financial Distress Altman, Springate, Grover Dan Ohlson Ppada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2011-2013 - Rini Tri Hastuti (Jurnal Ekonomi, 2015)
This study's purpose is to determine the most accurate bankruptcy prediction model in order to be suitable for use in its application to manufacturing companies in Indonesia and to determine whether there is a difference between Altman models with Springate models, Altman models with Grover models, and Altman models with Ohlson models. The scope of the study is limited to manufacturing industry companies listed on the Indonesia Stock Exchange during the years 2011-2013. This study compares four bankruptcy prediction models by using statistic descriptive analysis techniques also Kolmogorov-Smirnov normality test and paired test analysis techniques sample t-test with the help of the SPSS program. The conclusion of this study showed significant differences between the models Altman with Springate models, Altman models with Grover Â models, and Altman models with Ohlson models. And the highest level of accuracy was achieved by the Grover models.